Sensing characteristics of flame-spray-made Pt/ZnO thick films as H2 gas sensor - Nittaya Tamaekong (2018)
Hydrogen sensing of thick films of nanoparticles of pristine, 0.2, 1.0 and 2.0 atomic percentage of Pt concentration doped ZnO were investigated. ZnO nanoparticles doped with 0.2-2.0 at.% Pt were successfully produced in a single step by flame spray pyrolysis (FSP) technique using zinc naphthenate and platinum(II) acetylacetonate as precursors dissolved in xylene. The particle properties were analyzed by XRD, BET, SEM and TEM. Under the 5/5 (precursor/oxygen) flame condition, ZnO nanoparticles and nanorods were observed. The crystallite sizes of ZnO spheroidal and hexagonal particles were found to be ranging from 5 to 20 nm while ZnO nanorods were seen to be 5-20 nm wide and 20-40 nm long. ZnO nanoparticles paste composed of ethyl cellulose and terpineol as binder and solvent respectively was coated on Al2O3substrate interdigitated with gold electrodes to form thin films by spin coating technique. The thin film morphology was analyzed by SEM technique. The gas sensing properties toward hydrogen (H2) was found that the 0.2 at.% Pt/ZnO sensing film showed an optimum H2sensitivity of ~164 at hydrogen concentration in air of 1 volume% at 300 °C and a low hydrogen detection limit of 50 ppm at 300 °C operating temperature. © 2009 by the authors.